Jaminan Hukum Terhadap Merek Yang Terdaftar - Maruli Hutasoit; Sahadi Sahadi (International Forum of Researchers and Lecturers, 2024)
This study aims to review and analyze how the legal protection of registered trademarks and also why protection of registered trademarks can end. Trademarks or brand for producers is an image as well as a good name for the company, beside that it is also a part of the business strategy. There is no producer who does not use the brand as an identity for the goods they produced or the services they provided. The identity which is embodied in the mark is an identifier and at the same time becomes a differentiator to the others. This is why disputes often occurs against the brand. The research method uses a normative juridical. the results of this study that the registration of a mark may end due to the expiry of the validity period of the mark, the deletion of the mark due to request of the owner, the deletion of the registered mark at the initiative of the Minister after obtaining a recommendation from the Trademark Appeals Commission, and the deletion of the mark due to a lawsuit from a third party. The existence of trademark protection starts from the registration of the mark, protection of the mark during the period of the registration of the mark for 10 (ten) years and can be extended with the same period of time, there is legal action both in civil lawsuits, criminal prosecution and administrative steps in the form of refusal of trademark registration and deletion of brand.